Genesis of the rights and freedoms of the person as a component of the modern legal system - Головко, Світлана Григорівна; Бондаренко, Дар’я Юріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
This article contains the analysis of institutional development of human rights and liberties. There is adetermination of the basic factors for the fourth generation of rights and liberties formation in the conditionsof globalization and informatization in society. Modern approaches and main directions of this process in thenative law-creating are motivated.